Arti Korban Menurut Kitab Imamat - Ani Teguh Purwanto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2017)
Leviticus tells how sinful people can approach a holy God and how they live holy lives. To make atonement for their sins, God determines a series of sacrifices culminated in the sacrifices offered by the high priest. If you ignore the law and these statutes very severe punishment. Three core points: Yahweh dwells with the people of his choice, God is holy, so be holy Israel